Evaluation of Authentic Human Caring Professional Practices. (December 2015) - Brewer, Barbara B.; Watson, Jean
Abstract : OBJECTIVE: The aim of this study was to present an instrument and comparative database designed to evaluate patients' perceptions of caring behaviors of caregivers. BACKGROUND: Acute care leaders are under pressure to improve publicly reported patient satisfaction scores. Some nurse leaders have implemented professional practice environments based on human caring theory, whereas others have used scripting to standardize communication between staff and patients. METHODS: The Watson Caritas Patient Score (WCPS) is collected quarterly from a random sample of patients who are admitted to acute care hospital units. RESULTS: The WCPS was able to discriminate across unit types and hospitals. Items were related to publicly reported nursing communication scores. CONCLUSIONS: Participation in research based on human caring theory has given nurse leaders the opportunity to evaluate effectiveness of professional practice environments. It may provide the opportunity to focus staff communication with patients more authentically and in a way that enriches the experience for both.